Family typologies and styles of authority in the families of 6th grade students from three educational institutions in the Eje Cafetero (2021)
This research was carried out in three educational institutions in the Eje Cafetero. The objective is to understand the relationship between family typologies and styles of authority in families. It is a qualitative investigation, which included the survey, semi-structured interview and focus group instruments. The results show that the prevailing typology is extensive; the authority model, the democratic one, and there is no direct relationship between family typologies and authority models. It is believed necessary to create spaces that help parents and guardians to understand and analyze their parenting styles and clarify the exercise of authority.